Economic Cycle Forecasting as a Tool for Developing Anti-Cyclical Policy and Ensuring the Economic Security of Construction Enterprises - Shokotko, O (Ways to Improve Construction Efficiency, 2025)
The article substantiates the theoretical and methodological foundations for using economic cycle forecasting as a tool for the formation of anti-cyclical policy and ensuring the economic security of construction enterprises. It has been established that economic cyclicality is a determining factor in the functioning of construction enterprises, causing fluctuations in demand, investment activity, and financial performance. It is proven that the high sensitivity of the construction industry to the phases of the economic cycle increases the importance of implementing adaptive management mechanisms. The approach to the formation of anti-cyclical policy for construction enterprises has been improved. Unlike existing approaches, it is based on the integration of economic cycle forecasting into the decision-making process and involves the differentiation of management measures depending on the phase of the economic cycle. A conceptual model of anti-cyclical management for construction enterprises is proposed, which includes the stages of cycle forecasting, diagnosis of the economic cycle phase, development of appropriate management decisions, and evaluation of their effectiveness through a system of key performance indicators. In contrast to existing approaches, the model incorporates feedback between the achieved level of economic security and the adjustment of management decisions. It is substantiated that the assessment of the impact of anti-cyclical policy on the economic security of an enterprise should be carried out based on a system of financial and economic indicators, in particular liquidity, profitability, and financial stability, which makes it possible to comprehensively evaluate the enterprise’s ability to withstand crisis phenomena. It is proven that the implementation of anti-cyclical policy contributes to reducing investment, financial, and operational risks, increasing the adaptability of the enterprise to changes in the external environment, and ensuring the stability of its functioning. It is determined that the effectiveness of anti-cyclical policy directly depends on the quality of economic cycle forecasting, which necessitates the use of modern analytical tools to improve the validity of managerial decisions.